Role of Fe and Cr on the Structure and Activity of Pt/SO4-ZrO2 Used as Catalysts in n-pentane Isomerization. (5th October 2021) - Najafi, Shadi; Soltanali, Saeed; Nazemi, Ali Hekmat; Abbasi, Ali
Abstract : A Pt supported sulfated zirconia catalyst (SZ/Pt) was promoted by Fe and Cr via impregnation and co-participation methods. Firstly, the sulfated zirconia catalyst was evaluated to study its crystalline structure with different sulfuric acid ratios of 2:1, 5:1, 10:1, and 15:1. The catalyst appeared completely in the tetragonal phase at all acid ratios; except for 5:1. The state of the prepared catalyst was investigated by XRD, MAP, BET, TPD, FTIR, and TPR analyses. Incorporating Fe and Cr by impregnation method increases the surface area and acidity. In spite of increasing the acidity by loading Cr on SZ/Pt, the catalyst activity (conversion) decreases. Therefore, in this work increased inactivity is ascribed to the oxidative dehydrogenation activation. Among the prepared catalysts, the catalyst prepared by incorporating Fe and Cr by impregnation method (SZ/Fe-Cr-Pt) is the best catalyst in terms of catalytic activity. This sample increases the conversion 2.7 times compared with SZ/Pt.